(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Regular monitoring, proper shielding, and attention to safety procedures are all necessary for radiation safety in cyclotron facilities to reduce exposure and ensure regulatory compliance. This study investigates the radiation safety precautions taken at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) of Bangladesh Atomic Energy Commission (BAEC), during the operation of 18/9 MeV IBA Cyclone and synthesis of 18F-2-fluoro-2-deoxyglucose (18F-FDG). Portable survey meters and fixed Geiger-Muller (GM) counters were used to measure exposed dose of radiation in highly hazardous locations such as the cyclotron control room close to the vault and hot cell close to the synthesizers. Measurements were thoroughly carried out before, during, and following cyclotron operations. The findings showed that the hot cell room experienced radiation levels of 2.3 μSv/h during the synthesis of 18F-FDG, and the corridor vault experienced peak radiation levels of 2.0 μSv/h during the production of 18F. There was still activity present since post-operation values were higher than the baseline. When handling 18F-FDG, additional measurements at L-bench positions demonstrated the value of shielding and distance, with unshielded dose rates rising to 1.58 mSv/h. Safety precautions including radiation workers distance guidelines, ALARA (As Low As Reasonably Achievable) principles, and real-time monitoring were implemented to provide radiation protection. The results highlight the necessity of constant radiation monitoring, sufficient shielding, and rigorous adherence to radiation safety procedures to reduce occupational exposure and preserve regulatory compliance in medical cyclotron facilities. Bangladesh J. Nuclear Med. 28(1): 68-74, 2025